2009
DOI: 10.1002/ca.20889
|View full text |Cite
|
Sign up to set email alerts
|

The position of the mandibular canal and histologic feature of the inferior alveolar nerve

Abstract: The inferior alveolar nerve is the one of the large branches of the mandibular division of the trigeminal nerve. It is vulnerable during surgical procedures of the mandible. Despite its importance, no anatomical and histological examination has been conducted to provide a detailed cross-sectional morphology of the mandibular canal according to dental status. Therefore, the present study aimed to identify the position of the mandibular canal through direct measurement and to determine the branches of the inferi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
55
4
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(77 citation statements)
references
References 21 publications
7
55
4
4
Order By: Relevance
“…Accuracy of the studies evaluates anatomic structures of the maxillofacial region progress with the development of CBCT systems [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Accuracy of the studies evaluates anatomic structures of the maxillofacial region progress with the development of CBCT systems [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The mean maximum diameters of the mandibular canal, inferior alveolar nerve, inferior alveolar artery, and inferior alveolar vein were 2.52, 1.84, 0.42, and 0.58 mm, respectively. This study found that the inferior alveolar nerve often gives rise to several branches at each level (range 0-3) (39). There are also reports of concomitant absence of the ipsilateral inferior alveolar canal and mental foramen.…”
Section: Variations Of the Mandibular Nerve And Associated Complicationsmentioning
confidence: 48%
“…The safety zone takes into account that the coronal aspect of the mental foramen is approximately 2 mm above the inferior alveolar/ mental nerve so as to decrease the risk of paresthesia by inadvertent violation of the main trunk or its branches [13,14]. Hence, for example, a 12 mm long implant requires 14 mm of available bone height and a 9 mm long implant requires 11 mm of bone height.…”
Section: Discussionmentioning
confidence: 99%